Temporal variations landscape metrics of vegetation riparian areas in Gharesou River, Ardabil Province - Raoof Mostafazadeh; Fariba Esfandiary; Mahnaz Hamzeei; Nazila Alaei (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study was to evaluate the temporal variations of vegetation cover of Gharesou River riparian area in Ardabil province using landscape metrics over a period of 8 years which is important for morphology assessment and river ecosystem protection planning and management. The Google Earth imagery for the years 2011, 2016, 2019 due to their live view and high resolution were used to map the Gharesou River riparian area vegetation. Correlation analysis in R environment was used to evaluate the relationship between landscape metrics in the study time period. The results showed that there is an increase in the number of patches, which showed an increase in landscape fragmentation of the riparian area vegetation. Landscape connectivity index was 91.52% to 95.49% in this region during the study period, indicating the removing small patches of vegetation communities around the river. The number of patches in the present study showed an increasing trend, which was the highest amount at 2019 year. The results of changes in the width of the Gharesou River showed that the river width in 2019 was 27.43m and 3.97 m, respectively. Comparison of river width values ​​over the three study periods indicates an increasing trend in river widths, which may be due to the limitation of river width by human activities or the protection of river banks to protect agricultural lands against flooding effect. Also, the correlation of river width showed that the correlation between time period 2019 and 2016 was 0.63 and significant at 0.001 levels. The lowest correlation between the period 2019 and 2011 was 0.30 at 5% significant level. In conclusion, the results of changes in riparian area communities can be linked to the extension of agricultural land adjacent to the main river course.